Productivity, profitability and input-use efficiency of direct-seeded rice (Oryza sativa) under conservation agriculture - GHOSH, SOURAV; DAS, T K; RATHI, NEELMANI; RANA, K S; BISWAS, D R (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during kharif 2016-17 at ICAR-Indian Agricultural Research Institute, New Delhi to assess the long term impact of conservation agriculture (CA) on productivity, profitability and input-use efficiency of rice (Oryza sativa L.) under a rice-wheat cropping system (RWCS). Pooled results revealed that rice grain yield under the CA-based zero till direct seeded rice (ZTDSR) + mungbean residue (MR) – zero till wheat (ZTW) + rice residue (RR) – zero tilled summer mungbean (ZTM) + wheat residue (WR) both with 100% N (4.9 t/ha) and 75% N (4.8 t/ha) was statistically comparable to the conventional practice, i.e. transplanted puddled rice (TPR) – conventional till wheat (CTW) (5.2 t/ha) and TPR – ZTW (5.4 t/ha). Although rice grain yield under ZTDSR+MR–ZTW+RR– ZTM+WR [100% N] was 5.7% lower compared to farmers’ practice TPR–CTW, net returns of rice (₹ 41.1×103 / ha) was 119.5% higher compared to TPR-CTW, chiefly due to the lower cost of cultivation of ZT-DSR (₹ 47.5×103 / ha) as compared to CT-TPR (₹ 74.8×103 /ha). Partial factor productivity of NPK was highest under the CA treatment ZTDSR+MR–ZTW+RR–ZTM+WR [75% N] (32 kg grain/kg NPK) while ZTDSR+MR–ZTW+RR–ZTM+WR [75% N] [100% N] observed the highest irrigation water use efficiency (0.57 kg/m3). Thus, the novel CA practice ZTDSR+MR–ZTW+RR–ZTM+WR can provide comparable rice yields with higher net returns and nutrient (75% N) and irrigation use efficiencies compared to conventional farmers practice TPR–CTW and hence its adoption may be recommended.